2007
DOI: 10.1007/s10549-007-9595-7
|View full text |Cite
|
Sign up to set email alerts
|

Decision making in adjuvant trials in breast cancer: the NCIC CTG MA.17 trial as an example

Abstract: Decision-making regarding early closure and reporting of clinical trial results became a topic of intense debate following the reporting of the MA.17 adjuvant endocrine therapy trial. This trial was terminated at the first planned interim analysis when a highly significant improvement in disease free survival (DFS) was found. It has been suggested that the criterion for early stopping be made stricter when DFS is the primary study endpoint by ensuring that the targeted effect size is excluded. Our purpose is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Whether new treatment, such as the GnRh analogue plus aromatase inhibitor, improves the survival of the SNP-poor prognostic group compared to treatment with tamoxifen deserves further study. In addition, several studies have revealed that a longer duration of adjuvant hormonal therapy improves the survival of HR+ patients [1921], and host factors may be helpful in the selection of patients who may benefit more from longer duration of hormonal therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Whether new treatment, such as the GnRh analogue plus aromatase inhibitor, improves the survival of the SNP-poor prognostic group compared to treatment with tamoxifen deserves further study. In addition, several studies have revealed that a longer duration of adjuvant hormonal therapy improves the survival of HR+ patients [1921], and host factors may be helpful in the selection of patients who may benefit more from longer duration of hormonal therapy.…”
Section: Discussionmentioning
confidence: 99%
“…From a statistical standpoint, the MA.17 trial was designed with the assumption of a 4-year DFS rate of 88% in the placebo arm and for the detection of a 2.5% diVerence in this parameter with 80% power; this necessitated the enrollment of 4,800 women over 4 years with 2 years of follow-up and 515 events . Considering these predeWned parameters, it is important that the results of the Wrst interim analysis far exceeded these expectations, with a 6% diVerence in DFS between the groups (93 vs. 87%) after only 2.4 years, a highly signiWcant result (P = 0.00008) that clearly necessitated the early unblinding of the trial (Pater et al 2007). Letrozole is the Wrst and only AI thus far to demonstrate a signiWcant diVerence in DFS with acceptable tolerability as an extended adjuvant therapy for postmenopausal women with ER-positive early breast cancer in a randomized, appropriately designed, placebocontrolled trial.…”
Section: Comparing the Extended Adjuvant Ai Trialsmentioning
confidence: 99%